2020
DOI: 10.1177/0272431620919175
|View full text |Cite
|
Sign up to set email alerts
|

Individual and Social-Contextual Factors Underlying Adolescents’ Commitment to Victimizing Friendships: A Qualitative Analysis

Abstract: Previous research indicates that victimized youth are reluctant to address their friends’ victimizing behaviors and are likely to remain in a victimizing friendship despite experiencing significant distress. Research investigating the complex factors underlying this commitment to victimizing friendships is required. To this end, a qualitative research design was used as previously victimized youth asynchronously contributed to an anonymous online discussion forum for 2 months. Guided by two theories used to un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…A possible explanation for this result could be due to the normalization of these forms of violence. In a previous qualitative study (Bouchard et al, 2021), it was found that girls tend to normalize insults and behaviors aimed at damaging their reputation or social status because these actions are socially reinforced behaviors in different areas of their socialization, such as their favorite series or films. In addition, previous studies have pointed out that these behaviors are more difficult to detect and, in many cases, minimized even by the educational community itself (Bauman and Del Rio, 2006;Wójcik and Rzeńca, 2021), aspects that can hinder the victim's self-perception (Chen and Chen, 2019), making it difficult for them to seek help (Bastiaensens et al, 2015).…”
Section: Discussionmentioning
confidence: 97%
“…A possible explanation for this result could be due to the normalization of these forms of violence. In a previous qualitative study (Bouchard et al, 2021), it was found that girls tend to normalize insults and behaviors aimed at damaging their reputation or social status because these actions are socially reinforced behaviors in different areas of their socialization, such as their favorite series or films. In addition, previous studies have pointed out that these behaviors are more difficult to detect and, in many cases, minimized even by the educational community itself (Bauman and Del Rio, 2006;Wójcik and Rzeńca, 2021), aspects that can hinder the victim's self-perception (Chen and Chen, 2019), making it difficult for them to seek help (Bastiaensens et al, 2015).…”
Section: Discussionmentioning
confidence: 97%
“…The third paper in the special issue explores victimization within friendships. Drawing from knowledge about another type of relationship characterized by positive features as well as power-oriented aggression, Bouchard, Smith, and Woods (2020) apply theories of intimate partner violence to understand why adolescents continue relationships with friends who bully them. Twenty-five previously victimized youth wrote about their experiences in victimizing friendships via an anonymous online discussion forum.…”
mentioning
confidence: 99%